Soluble C-Type Lectin-Receptor Ligands Stimulate ROS Production in Dendritic Cells and Potentiate Killing of MRSA as Well as the MRSA Induced IL-12 Production - Eld, Helene M. S.; Johnsen, Peter R.; Nielsen, Emilie M.; Jørgensen, Frederikke Z.; Lindstrøm-Svendsen, Marie; Baldry, Mara; Ingmer, Hanne; Frøkiær, Hanne (Frontiers in Immunology, 2022)
Abstract Methicillin resistant Staphylococcus aureus (MRSA) has developed resistance to most β-lactam antibiotics leaving few treatment options against infections with MRSA. Through the mannose receptor, mannan potentiates IL-12 production induced by Gram-positive bacteria and crucial in clearance of S. aureus infection. We investigated the IL-12 potentiating effect of mannan pre-treatment of bone marrow-derived dendritic cells prior to stimulation with clinical MRSA strains. Mannan almost doubbled IL-12 as well as IFN- production in response to USA300, also if USA300 was treated with the -lactam cefoxitin. The MRSA induced IL-12 production was dependent on bacterial uptake and ROS production. Mannan alone induced ROS production, and in combination with USA300, the ROS production corresponded to the sum induced by mannan and USA300. Mannan addition further increased the endocytosis as well as the rate of endosomal killing of bacteria. Addition of a monoclonal antibody against MR or solluble dectin-1 ligands likewise induced ROS and potentiated the USA300 induced IL-12 production. In the presence of the pro-inflammatory mediators, GM-CSF or IFN-b, the mannan enhanced IL-12 production increased further. The USA300 induced and the MR facilitated enhanced IFN-b and IL-12 showed same dependency on MAPK c-jun N-terminal kinase signaling , suggesting that mannan enhances the signals already induced by the bacteria, rather than changing them. We suggest that the C-lectin-induced ROS production is a key factor in the IFN-b and IL-12 potentiation.